2012
DOI: 10.13073/fpj-d-12-00101.1
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Roundwood Utilization Rates in West Virginia

Abstract: Forest harvesting is an integral part of the West Virginia forest economy. This component of the supply chain supports a diverse array of primary and secondary processors. A key metric used to describe the efficiency of the roundwood extraction process is the logging utilization factor (LUF). The LUF is one way managers can discern the overall use of harvested roundwood. To update LUF in West Virginia, roundwood utilization during harvesting operations was investigated on 30 active sites in 2008. Approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Yellow-poplar test samples were selected given the prevalence of yellow-poplar harvesting (25.5%) in West Virginia (Grushecky et al 2012) and historical use by the forest products industry (Wiemann 2010). A freshly cut yellow-poplar log (diameter ¼ 175 6 15 mm, length ¼ 900 6 20 mm) was procured from the West Virginia University Research Forest.…”
Section: Materials and Methods Procurement And Processing Of Raw Materialsmentioning
confidence: 99%
“…Yellow-poplar test samples were selected given the prevalence of yellow-poplar harvesting (25.5%) in West Virginia (Grushecky et al 2012) and historical use by the forest products industry (Wiemann 2010). A freshly cut yellow-poplar log (diameter ¼ 175 6 15 mm, length ¼ 900 6 20 mm) was procured from the West Virginia University Research Forest.…”
Section: Materials and Methods Procurement And Processing Of Raw Materialsmentioning
confidence: 99%
“…The USFS Forest Inventory and Analysis Program (FIA) is conducting similar logging utilization studies in many parts of the country. In West Virginia, Grushecky et al [15] found that 100 % of 30 active logging jobs produced wood waste, with an overall roundwood utilization rate of 87 %, with in-woods and landing utilization variable by species. Results indicated that roundwood residues were a relatively small component of the potentially available biomass associated with operations, especially at the landing, in large part because of the diverse markets available to loggers in this area.…”
Section: Innovative Processes and Practicesmentioning
confidence: 99%
“…The stumpage, however, can also be purchased and harvested by independent loggers or purchased by log brokers before being sold to the sawmill. Typically, hardwood sawmills in the United States procure logs within 25 to 100 miles of the mill, depending on product requirements, log availability, and production needs (Anderson and Germain 2007;Anderson 2008;Grushecky et al 2011;Grushecky et al 2012). Fragmentation of private forestlands, exploitative harvesting practices, changes in landowner objectives in favor of recreational and conservation values, and the decreasing number of logging companies (Kenefic and Nyland 2005;Anderson and Germain 2007;Timber Harvesting 2011;Riitters et al 2012), have negatively affected the ability of sawmills to find reliable, consistent sources of logs in close proximity to their mills.…”
Section: Research Backgroundmentioning
confidence: 99%